Strong Convergence Theorems for Asymptotically Strict Pseudocontractive Mappings in the Intermediate Sense: Jerry N. Ezeora, Yekini Shehu - Team, Support (Thai Journal of Mathematics, 2011)
In this paper, we introduce two hybrid iteration schemes and obtain strong convergence theorems for an infinite family of uniformly continuous asymptotically λ-strict pseudocontractive mappings in the intermediate sense in a real Hilbert space.